Nutritional characterization of gluten free non-traditional pasta - Milde, Laura Beatríz (2018)
When a food is formulated, its characterization is important from the chemical and biochemical point of view; even more whennon-traditional raw materials are used. Noodles were made with cassava starch and corn flour (4:1), milk, egg, salt and xanthangum. The chemical composition of the pasta was determined and the total and resistant starch content was quantified. Thehydrolysis rate of the starch was measured at different times, from which the hydrolysis index and, subsequently, the predictiveglycemic index was calculated. The chemical composition of the noodles showed its high content of total fibers. From thedigestibility tests, high values were obtained for proteins (93%), and average values for the starch (52%). The results of the starchhydrolysis kinetics showed a higher proportion of slowly digestible starch with a low glycemic index (46%). Analyzed noodles arewithin the dietary guidelines that suggest a diet with high total dietary fiber content and low glycemic index.